Comparative study on the accelerated thermal aging behavior between palm and rapeseed natural ester oils - N. L. M. Ridzuan; N. A. Bakar; S. A. Ghani; I. S. Chairul; N. H. A. Aziz (Bulletin of Electrical Engineering and Informatics, 2019)
The suitability of natural ester oils as an insulating medium in power transformers is discussed in this paper. Owing to environmental concerns, natural ester oils have great potential as mineral oil substitutes in power transformers. In this paper, the aging behaviors of palm and rapeseed natural ester oils were compared with that for mineral oil. The performance of these natural ester oils was assessed based on their properties (moisture content, acidity, and relative content of dissolved decay products) after accelerated thermal aging. The results showed that the palm oil has better performance compared to the rapeseed oil after accelerated thermal aging for 1500 h because of its lower acidity. This was further supported by the presence of sludge in the rapeseed oil after 1500 h of aging.